Before the storm : American Indians before the Europeans - Lassieur, Allison (New York : Facts on File, 1998)
A narrative history about the various Indian people of North America and their way of life before contact with Europeans
Includes bibliographical references and index
Keywords: Indians of North America -- Juvenile literature; Indians of North America